2018
DOI: 10.1111/jftr.12274
|View full text |Cite
|
Sign up to set email alerts
|

Research on Fathers in the Military Context: Current Status and Future Directions

Abstract: Fathering in the military context has been studied for decades. The general approach to this research has mirrored the way in which civilian fathering was studied, with an original emphasis on the deficiencies among fathers as parents, eventually giving way to examining the benefits of father involvement. Largely in the past decade, research has begun to examine the strengths of military fathers and how they can thrive as parents even as they live in a challenging work context. This review examines the litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 72 publications
(136 reference statements)
1
10
0
Order By: Relevance
“…Although much of the research related to military fathers has focused on parent or child dysfunction, there is a growing body of research that focuses on the families that thrive (Karre et al, 2018). The findings in this study support previous research that has found that social support and couple adjustment are related to parenting (Gewirtz et al, 2010).…”
Section: Discussion Limitations and Future Directionssupporting
confidence: 80%
See 1 more Smart Citation
“…Although much of the research related to military fathers has focused on parent or child dysfunction, there is a growing body of research that focuses on the families that thrive (Karre et al, 2018). The findings in this study support previous research that has found that social support and couple adjustment are related to parenting (Gewirtz et al, 2010).…”
Section: Discussion Limitations and Future Directionssupporting
confidence: 80%
“…This investigation, however, will examine recent active duty veterans. Fathers, specifically, are being examined as there has been a dearth of research on the positive behaviors in which military fathers engage (Karre et al, 2018). The strengths-based approach taken here will expand on the literature related to positive father involvement of military fathers, and it will also inform on what protective factors could help fathers who are struggling with parenting after a combat deployment.…”
Section: Present Studymentioning
confidence: 99%
“…Upon his return and increased involvement, the family system may feel that their adaptability is hindered, potentially altering family flexibility. During these times of change and disorganization, the marital relationship may be a key factor for family‐level and individual‐level outcomes (Karre et al, 2018).…”
Section: Figurementioning
confidence: 99%
“…relationship may be a key factor for family-level and individual-level outcomes (Karre et al, 2018).…”
Section: Fathers' Involvement and Family Flexibilitymentioning
confidence: 99%
See 1 more Smart Citation